2023
DOI: 10.1039/d3nj01720f
|View full text |Cite
|
Sign up to set email alerts
|

High performance cathode materials for lithium-ion batteries based on a phenothiazine-based covalent triazine framework

Abstract: As a novel class of robust redox-active organic polymers, covalent triazine frameworks (CTFs) are highly promising cathode materials for lithium-ion batteries. However, the low electronic conductivity, low redox potentials, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Enhanced rate performance can be achieved by preparation compounds with high conductivity or by combining nitrogen-centered materials with highly conductive substances, such as graphene and carbon nanotubes (CNTs). [58,59] On the other hand, the high solubility of nitrogen-centered compounds causes continuous loss of active materials and rapid capacity decay during cycling. Four effective strategies are proposed to suppress the dissolution of nitrogen-centered materials: 1) polymerization, which involves creating polymerized nitrogen-redox-center compounds to increase molecular weight and mitigate dissolution issues of smaller structures; [60] 2) salification, wherein compounds (e.g., COOM, M = Li, Na, K) with high polarity exhibit low solubility in aprotic electrolytes; [52] 3) hybridization with insoluble species, for instance, Lin et al reported that the poly(2,2,6,6-tetramethylpiperidin-1-oxyl-4ylmethacrylate) (PTMA) brushed on silica nanoparticles delivered a better cycling performance (96.3% capacity retention after 300 cycles) compared to the PTMA composite cathodes (81.9% capacity retention at the same conditions) for the reduced dissolution of PTMA active material; [61] (4) electrolyte optimization.…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…Enhanced rate performance can be achieved by preparation compounds with high conductivity or by combining nitrogen-centered materials with highly conductive substances, such as graphene and carbon nanotubes (CNTs). [58,59] On the other hand, the high solubility of nitrogen-centered compounds causes continuous loss of active materials and rapid capacity decay during cycling. Four effective strategies are proposed to suppress the dissolution of nitrogen-centered materials: 1) polymerization, which involves creating polymerized nitrogen-redox-center compounds to increase molecular weight and mitigate dissolution issues of smaller structures; [60] 2) salification, wherein compounds (e.g., COOM, M = Li, Na, K) with high polarity exhibit low solubility in aprotic electrolytes; [52] 3) hybridization with insoluble species, for instance, Lin et al reported that the poly(2,2,6,6-tetramethylpiperidin-1-oxyl-4ylmethacrylate) (PTMA) brushed on silica nanoparticles delivered a better cycling performance (96.3% capacity retention after 300 cycles) compared to the PTMA composite cathodes (81.9% capacity retention at the same conditions) for the reduced dissolution of PTMA active material; [61] (4) electrolyte optimization.…”
Section: Challenges and Solutionsmentioning
confidence: 99%